Once, Only Once, and in the Right Place: Residence Rules in the Decennial Census - National Research Council (The National Academies Press, 2006)
The usefulness of the U.S. decennial census depends critically on the accuracy with which individual people are counted in specific housing units, at precise geographic locations. The 2000 and other recent censuses have relied on a set of residence rules to craft instructions on the census questionnaire in order to guide respondents to identify their correct &#34usual residence.&#34 Determining the proper place to count such groups as college students, prisoners, and military personnel has always been complicated and controversial; major societal trends such as placement of children in shared custody arrangements and the prevalence of &#34snowbird&#34 and &#34sunbird&#34 populations who regularly move to favorable climates further make it difficult to specify ties to one household and one place. Once, Only Once, and in the Right Place reviews the evolution of current residence rules and the way residence concepts are presented to respondents. It proposes major changes to the basic approach of collecting residence information and suggests a program of research to improve the 2010 and future censuses.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Testing of Defense Systems in an Evolutionary Acquisition Environment - National Research Council (The National Academies Press, 2006)
The Department of Defense (DoD) recently adopted evolutionary acquisition, a dynamic strategy for the development and acquisition of its defense systems. Evolutionary defense systems are planned, in advance, to be developed through several stages in a single procurement program. Each stage is planned to produce a viable system which could be fielded. The system requirements for each stage of development may be specified in advance of a given stage or may be decided at the outset of that stage's development. Due to the different stages that comprise an evolutionary system, there exists a need for careful reexamination of current testing and evaluation policies and processes, which were designed for single-stage developments.
Keywords: Conflict and Security Issues

Letter Report to Sir Michael Marmot on the Social Determinants of Health - National Research Council (The National Academies Press, 2006)

America's Lab Report: Investigations in High School Science - National Research Council (The National Academies Press, 2006)
Laboratory experiences as a part of most U.S. high school science curricula have been taken for granted for decades, but they have rarely been carefully examined. What do they contribute to science learning? What can they contribute to science learning? What is the current status of labs in our nationï¿½s high schools as a context for learning science? This book looks at a range of questions about how laboratory experiences fit into U.S. high schools:
Keywords: Education

Multiple Origins, Uncertain Destinies: Hispanics and the American Future - National Research Council (The National Academies Press, 2006)
Given current demographic trends, nearly one in five U.S. residents will be of Hispanic origin by 2025. This major demographic shift and its implications for both the United States and the growing Hispanic population make Multiple Origins, Uncertain Destinies a most timely book. This report from the National Research Council describes how Hispanics are transforming the country as they disperse geographically. It considers their roles in schools, in the labor market, in the health care system, and in U.S. politics.
Keywords: Behavioral and Social Sciences

Child Health in Complex Emergencies - National Research Council (The National Academies Press, 2006)
Addressing the health needs of children in complex emergencies is critical to the success of relief efforts and requires coordinated and effective interventions. However, little systematic work has been undertaken to evaluate such care. To address this need, this monograph presents a review of the published literature in this area, providing background on the burden of disease, the major causes of morbidity and mortality, and the evidence base for effective interventions. It also describes surveys of nongovernmental organizations (NGOs) and international agencies providing care to children in complex emergencies, which were conducted to identify guidelines commonly used to provide such care and assesses the content and limitations of these guidelines. A more in-depth survey of several organizations was also conducted to assess obstacles to this kind of care.
Keywords: Health and Medicine

When I'm 64 - National Research Council (The National Academies Press, 2006)
By 2030 there will be about 70 million people in the United States who are older than 64. Approximately 26 percent of these will be racial and ethnic minorities. Overall, the older population will be more diverse and better educated than their earlier cohorts. The range of late-life outcomes is very dramatic with old age being a significantly different experience for financially secure and well-educated people than for poor and uneducated people. The early mission of behavioral science research focused on identifying problems of older adults, such as isolation, caregiving, and dementia. Today, the field of gerontology is more interdisciplinary. When I'm 64 examines how individual and social behavior play a role in understanding diverse outcomes in old age. It also explores the implications of an aging workforce on the economy. The book recommends that the National Institute on Aging focus its research support in social, personality, and life-span psychology in four areas: motivation and behavioral change; socioemotional influences on decision-making; the influence of social engagement on cognition; and the effects of stereotypes on self and others. When I'm 64 is a useful resource for policymakers, researchers and medical professionals.
Keywords: Behavioral and Social Sciences; Health and Medicine

Food Insecurity and Hunger in the United States: An Assessment of the Measure - National Research Council (The National Academies Press, 2006)
The United States is viewed by the world as a country with plenty of food, yet not all households in America are food secure, meaning access at all times to enough food for an active, healthy life. A proportion of the population experiences food insecurity at some time in a given year because of food deprivation and lack of access to food due to economic resource constraints. Still, food insecurity in the United States is not of the same intensity as in some developing countries. Since 1995 the U.S. Department of Agriculture (USDA) has annually published statistics on the extent of food insecurity and food insecurity with hunger in U.S. households. These estimates are based on a survey measure developed by the U.S. Food Security Measurement Project, an ongoing collaboration among federal agencies, academic researchers, and private organizations.
Keywords: Food and Nutrition; Behavioral and Social Sciences; Surveys and Statistics

Analyzing the U.S. Content of Imports and the Foreign Content of Exports - National Research Council (The National Academies Press, 2006)
Mass media has frequently covered stories concerning "outsourcing" or the moving of U.S. jobs to foreign locations by U.S. multinational companies. More often than not this "outsourcing" is of benefit to the companies' owners and managers. The discussion has spilled over into the political debate with candidates for national office making statements and suggesting policies for dealing with the issue.
Keywords: Industry and Labor

Hispanics and the Future of America - National Research Council (The National Academies Press, 2006)
Hispanics and the Future of America presents details of the complex story of a population that varies in many dimensions, including national origin, immigration status, and generation. The papers in this volume draw on a wide variety of data sources to describe the contours of this population, from the perspectives of history, demography, geography, education, family, employment, economic well-being, health, and political engagement. They provide a rich source of information for researchers, policy makers, and others who want to better understand the fast-growing and diverse population that we call “Hispanic.” The current period is a critical one for getting a better understanding of how Hispanics are being shaped by the U.S. experience. This will, in turn, affect the United States and the contours of the Hispanic future remain uncertain. The uncertainties include such issues as whether Hispanics, especially immigrants, improve their educational attainment and fluency in English and thereby improve their economic position; whether growing numbers of foreign-born Hispanics become citizens and achieve empowerment at the ballot box and through elected office; whether impending health problems are successfully averted; and whether Hispanics’ geographic dispersal accelerates their spatial and social integration. The papers in this volume provide invaluable information to explore these issues.
Keywords: Behavioral and Social Sciences

Assessing Fitness for Military Enlistment: Physical, Medical, and Mental Health Standards - National Research Council (The National Academies Press, 2006)
The U.S. Department of Defense (DoD) faces short-term and long-term challenges in selecting and recruiting an enlisted force to meet personnel requirements associated with diverse and changing missions. The DoD has established standards for aptitudes/abilities, medical conditions, and physical fitness to be used in selecting recruits who are most likely to succeed in their jobs and complete the first term of service (generally 36 months). In 1999, the Committee on the Youth Population and Military Recruitment was established by the National Research Council (NRC) in response to a request from the DoD. One focus of the committee's work was to examine trends in the youth population relative to the needs of the military and the standards used to screen applicants to meet these needs.
Keywords: Health and Medicine; Conflict and Security Issues; Behavioral and Social Sciences

Systems for State Science Assessment - National Research Council (The National Academies Press, 2006)
In response to the No Child Left Behind Act of 2001 (NCLB), Systems for State Science Assessment explores the ideas and tools that are needed to assess science learning at the state level. This book provides a detailed examination of K-12 science assessment: looking specifically at what should be measured and how to measure it.
Keywords: Education

Supporting Local Health Care in a Chronic Crisis: Management and Financing Approaches in the Eastern Democratic Republic of the Congo - National Research Council (The National Academies Press, 2006)
Providing medical support to the local population during a chronic crisis is difficult. The crisis in the Democratic Republic of the Congo (DRC), which is characterized by high excess mortality, ongoing armed violence, mass forced displacement, interference by neighboring countries, resource exploitation, asset stripping, and the virtual absence of the state, has led to great poverty and a dearth of funds for the support of the health system.
Keywords: Health and Medicine

ICT Fluency and High Schools: A Workshop Summary - National Research Council (The National Academies Press, 2006)
Information and communications technology (ICT) pervades virtually all domains of modern life—educational, professional, social, and personal. Yet although there have been numerous calls for linkages that enable ICT competencies acquired in one domain to benefit another, this goal has largely remained unrealized. In particular, while technology skills and applications at work could be greatly enhanced by earlier complementary learning at school—particularly in K-12 education, a formative and influential stage in a person's life—little progress has been made on such linkages. At present, the curricula of most U.S. high schools focus on skills in the use of tools such as specific word-processing software or contemporary Internet search engines. Although these kinds of skills are certainly valuable—at least for a while—they comprise just one component, and the most rudimentary component, of ICT competencies.
Keywords: Education

Improving Business Statistics Through Interagency Data Sharing: Summary of a Workshop - National Research Council (The National Academies Press, 2006)
U.S. business data are used broadly, providing the building blocks for key national—as well as regional and local—statistics measuring aggregate income and output, employment, investment, prices, and productivity. Beyond aggregate statistics, individual- and firm-level data are used for a wide range of microanalyses by academic researchers and by policy makers. In the United States, data collection and production efforts are conducted by a decentralized system of statistical agencies. This apparatus yields an extensive array of data that, particularly when made available in the form of microdata, provides an unparalleled resource for policy analysis and research on social issues and for the production of economic statistics. However, the decentralized nature of the statistical system also creates challenges to efficient data collection, to containment of respondent burden, and to maintaining consistency of terms and units of measurement. It is these challenges that raise to paramount importance the practice of effective data sharing among the statistical agencies.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Surveys and Statistics

Food Marketing to Children and Youth: Threat or Opportunity? - Institute of Medicine (The National Academies Press, 2006)
Creating an environment in which children in the United States grow up healthy should be a high priority for the nation. Yet the prevailing pattern of food and beverage marketing to children in America represents, at best, a missed opportunity, and at worst, a direct threat to the health prospects of the next generation. Children’s dietary and related health patterns are shaped by the interplay of many factors—their biologic affinities, their culture and values, their economic status, their physical and social environments, and their commercial media environments—all of which, apart from their genetic predispositions, have undergone significant transformations during the past three decades. Among these environments, none have more rapidly assumed central socializing roles among children and youth than the media. With the growth in the variety and the penetration of the media have come a parallel growth with their use for marketing, including the marketing of food and beverage products. What impact has food and beverage marketing had on the dietary patterns and health status of American children? The answer to this question has the potential to shape a generation and is the focus of Food Marketing to Children and Youth. This book will be of interest to parents, federal and state government agencies, educators and schools, health care professionals, industry companies, industry trade groups, media, and those involved in community and consumer advocacy.
Keywords: Food and Nutrition

Studying Media Effects on Children and Youth: Improving Methods and Measures: Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2006)
The presence and intensity of media influences television, radio, music, computers, films, videos, and the Internet are increasingly recognized as an important part of the social ecology of children and youth, and these influences have become more visible and volatile in recent decades. Research that explores the level and effects of media influences calls for measurements of the quantity and character of exposure to a variety of potentially overlapping media sources, an analysis of the content of the media output, and examination of the social context and relationships that are associated with the media experience.
Keywords: Behavioral and Social Sciences; Computers and Information Technology

A Study of Interactions: Emerging Issues in the Science of Adolescence: Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2006)
Scholars--and adults in general--have pondered for centuries the mysterious processes that influence the ways in which children gradually become adults. The development of professional organizations and journals devoted to adolescence, as well as increasing appreciation in academia and the world of policy for the importance of this phase of life, have helped this field catch up with the pace of research on other stages of human development particularly infancy and early childhood.
Keywords: Behavioral and Social Sciences; Health and Medicine